2021
DOI: 10.1097/md.0000000000027092
|View full text |Cite
|
Sign up to set email alerts
|

Role of geospatial mapping in the planning of HIV programs

Abstract: Geographic information systems (GIS) tools can be used to understand the spatial distribution of local HIV epidemics but are often underutilized, especially in low-middle income countries. We present characteristics of an HIV epidemic within Hyderabad, a large city in southern India, as a case study to highlight the utility of such data in program planning. Cross-sectional sample recruited using respondent-driven sampling in a cluster-randomized trial. We analyzed data from 2 cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Figure 4 shows that 37% (n = 65) of the articles focused on reporting STI/HIV prevalence estimates [3047] and correlates of HIV-related risk behaviors [48–94] among MSM and TGW. In the 18 studies [3047] that reported HIV and STI prevalence estimates among MSM and TGW, nine [31-33, 37, 3942, 45] were conducted in clinical settings, six [30, 34, 35, 38, 43, 46] in community settings, and three [36, 44, 47] in both clinical and community settings. Of these 18 studies, eight [30, 34, 35, 37, 40, 43, 45, 46] reported HIV/STI prevalence and risk factors among MSM, three [36, 39, 44] human papillomavirus (HPV) prevalence among MSM living with HIV, and three [31, 33, 45] reported prevalence of perianal dermatoses, HPV and other STIs (such as syphilis, chlamydia and gonorrhea) among MSM.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 4 shows that 37% (n = 65) of the articles focused on reporting STI/HIV prevalence estimates [3047] and correlates of HIV-related risk behaviors [48–94] among MSM and TGW. In the 18 studies [3047] that reported HIV and STI prevalence estimates among MSM and TGW, nine [31-33, 37, 3942, 45] were conducted in clinical settings, six [30, 34, 35, 38, 43, 46] in community settings, and three [36, 44, 47] in both clinical and community settings. Of these 18 studies, eight [30, 34, 35, 37, 40, 43, 45, 46] reported HIV/STI prevalence and risk factors among MSM, three [36, 39, 44] human papillomavirus (HPV) prevalence among MSM living with HIV, and three [31, 33, 45] reported prevalence of perianal dermatoses, HPV and other STIs (such as syphilis, chlamydia and gonorrhea) among MSM.…”
Section: Resultsmentioning
confidence: 99%
“…In the 18 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] that reported HIV and STI prevalence estimates among MSM and TGW, nine [31-33, 37, 39-42, 45] were conducted in clinical settings, six [30,34,35,38,43,46] in community settings, and three [36,44,47] in both clinical and community settings. Of these 18 studies, eight [30,34,35,37,40,43,45,46] reported HIV/STI prevalence and risk factors among MSM, three [36,39,44] human papillomavirus (HPV) prevalence among MSM living with HIV, and three [31,33,45] reported prevalence of perianal dermatoses, HPV and other STIs (such as syphilis, chlamydia and gonorrhea) among MSM. Two studies [38,47] reported correlates of HIV incidence among MSM, with one study each reporting Hepatitis C prevalence among MSM living with HIV…”
Section: Hiv/sti Prevalence and Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations